Cardiorespiratory Fitness and Its Place in Medicine - Robert Ross; Jonathan Myers (Reviews in Cardiovascular Medicine, 2023)
The evidence that cardiorespiratory fitness (CRF) predicts morbidity and mortality independent of commonly obtained risk factors is beyond dispute. Observations establishing that the addition of CRF to algorithms for estimating cardiovascular disease risk reinforces the clinical utility of CRF. Evidence suggesting that non-exercise estimations of CRF are associated with all-cause mortality provides an opportunity to obtain estimates of CRF in a cost-effective manner. Together with the observation that CRF is substantially improved in response to exercise consistent with guideline recommendations underscores the position that CRF should be included as a routine measure across all health care settings. Here we provide a brief overview of the evidence in support of this position.